Empowering Village Krama Councils in Preventing Child Marriage: A Study of Policy Synergy on North Lombok - Mariani, Dina; Hadi, Imron; Putri, Suci Ramadhani; Aminah, Siti (Al-Mujtahid: Journal of Islamic Family Law, 2025)
This qualitative study explores the role of Village Councils in preventing child marriage on Lombok Island, focusing specifically on policy synergy and local governance. This research uses Lawrence M. Friedman's legal system theory to analyze the impact of regional regulations and community-based initiatives in addressing child marriage in North Lombok Regency, West Nusa Tenggara Province, Indonesia. This study adopts an empirical juridical approach, with primary data from North Lombok Regent Regulation No. 20/2017 on Village Council Guidelines and secondary data from relevant literature. Despite significant efforts, child marriage remains a widespread issue on the island. The North Lombok Regency Government, through the empowerment of Village Krama Councils, has made substantial progress in addressing this issue. However, challenges persist, including unclear regulatory provisions and inconsistent application of Village Council functions across the region. The strong legal culture and the tradition of deliberation for consensus within the local community play a crucial role in the success of these initiatives. This study emphasizes the importance of empowering Village Councils to enhance the effectiveness of policies and further reduce child marriage practices in Lombok.